KONTRIBUSI KELUARGA TERHADAP PEMBENTUKAN KARAKTER ANAK (Studi Perspektif Modal Sosial di Kota Parepare) - Anwar, Anwar (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2016)
This article analyzed empirically about education character that was applied and developed by success family toward children education, the education that concern on social modal development. Family has function to lay the strong basics about social modal values that are needed by the children. When all of the elements of characters are absorbed by the children, then it becomes integral part in personality reconstruction, basically is the interaction result from system and behavior patterns that practiced by the parents. Family education basic determined the child succeed, depended on behavior patterns and interaction that developed by the parents. Family which has strong behavior patterns created the religious climate is the family that can make a role in an optimal fashion in developing the education of social modal oriented. While the family which is developed liberal behavior patterns, authoritative and ignored the religious climate, showed the low indication of role and function towards social modal development.